EVIDENŢIEREA INFLUENŢEI PREPARATULUI MELANGOZIDĂ – O ÎN COMBINAŢIE CU MICROELEMENTE ASUPRA INTENSITĂŢII UNOR PROCESE FIZIOLOGICE LA POMII DE MĂR - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2010)
The researches carried out in the garden conditions, in the greenhouse with an optimal regime of soil humidity, there but were revealed significant influences of foliar use of the preparation Melangozida – O of natural origin in combination with the microelements Zn an B on the activity of photosynthetic and enzymatic apparatus, accumulation of carbohydrates in the leafs of formations, fructiferous vegetative growth and fruiting of apple trees. As the result metabolic processes are favorable for the launching of floral induction. In the conditions of greenhouse the used treatments contributed to the accumulation of carbohydrates in leafs at orchards inoculated with brachytic tree stock.